Proto-oncogene analysis in multiple myeloma. - Ladanyi, M. (1992)
The genetic basis for the development of multiple myeloma (MM) remains poorly understood, in part because MM has thus far been relatively refractory to cytogenetic analysis. The few cases karyotyped have pointed to involvement of 11q13, site of the BCL1 proto-oncogene, or of 8q24, site of the MYC proto-oncogene. A recent molecular study detected rearrangements distal to the MYC gene in 16% of MM, using the MLVI-4 probe. The immunocytochemical demonstration of BCL2 protein overexpression in at least some cases of MM has suggested the possibility of translocation-mediated deregulation of the BCL2 proto-oncogene. The configuration of the BCL2 gene in MM, however, has not yet been defined using all available breakpoint probes. To address these issues, we studied 17 patients with plasma cell dyscrasias (16 MM, 1 plasmacytoma) by Southern blotting using the major breakpoint region (MBR), minor cluster region (MCR), and 5' cDNA (pB16) BCL2 breakpoint probes; with the BCL1 major translocation cluster (MTC) breakpoint probe; and with a probe to the MYC-associated MLVI-4 region (PA1.3SB). In all 17 cases, rearrangement of one or both alleles of the immunoglobulin heavy chain gene had been demonstrated, thereby confirming the presence of tumor DNA in the samples studied. None of the cases tested showed a rearrangement with the MBR BCL2 (0/16), MCR BCL2 (0/17), 5' cDNA BCL2 (0/16), BCL1 MTC (0/15), or MLVI-4 (0/15) probes. These results suggest that if BCL2 deregulation does indeed occur in MM, a mechanism other than translocation must be involved in most cases. Furthermore, rearrangements distal to the MYC gene, in the region of the MLVI-4 probe, may be less common than previously thought. Finally, a significant proportion of translocation breakpoints in band 11q13 may not be detected by the BCL1 MTC probe in MM, as is true in lymphomas.